CORRELATION OF PUCAI BETWEEN MAYO ENDOSCOPIC AND GEBOES PATHOLOGY SCORES IN ASSESSING DISEASE ACTIVITY OF PEDIATRIC PATIENTS WITH UC AMONG HISPANICS AND NON-HISPANICS. (22nd January 2022) - Durazo, Francisco; Michail, Sonia
Abstract: BACKGROUND: Disease activity in ulcerative colitis (UC) has traditionally been assessed by clinical scoring systems, including the pediatric ulcerative colitis activity index (PUCAI), a non-invasive, reliable way to monitor disease severity and the therapeutic efficacy of interventions in pediatric UC. Practice guidelines have recommended the use of PUCAI in routine clinical pediatric care. Therefore, we aim to investigate the correlation of PUCAI with the endoscopic assessment of disease activity (Mayo endoscopic score) and histologic features of mucosal inflammation (Geboes pathology grading score) in a Hispanic pediatric UC population compared to a non-Hispanic pediatric population. METHODS: We conducted a retrospective study in pediatric patients aged 7 - 21 with UC enrolled at Children's Hospital of Los Angeles. We first assess the distribution of the PUCAI, the Mayo, and the Geboes grading scales of disease activity (0=remission, 1=mild, 2=moderate, 3=severe) of the Physician Global Assessment (PGA). Reviewed data was collected directly from the physician report or calculated retrospectively using clinic notes. Although different pathologists graded the samples, the Geboes score is used as a department-wide standard for grading UC. Spearman correlation coefficient was assessed to measure the degree of linear association between two order-valued variables. Bootstrap simulations were used to calculate 95% confidence intervals, and approximate permutation tests were applied to compare these correlations between Hispanics and Non-Hispanics. RESULTS: In total, 172 patients fit our inclusion criteria. Overall, a modest correlation between PUCAI with the Mayo endoscopic and Geboes pathology grading scores was observed (0.72 and 0.68). The PUCAI-Endoscopic correlations were 0.65 and 0.79 for Hispanics and non-Hispanics, respectively (p-value of difference = 0.084). The correlations between Geboes pathology and PUCAI grading scores were weaker but still larger for non-Hispanics (0.73) than Hispanics (0.64). A linear relationship between PUCAI scores and the two gradings scores, Mayo endoscopy and Geboes pathology, is shown in Figure 1 (p for trend < 0.001). CONCLUSION: Endoscopic/pathology disease severity generally correlates with clinical disease activity measured by PUCAI score. The PUCAI correlated well with the endoscopy/pathology scores in severe clinical disease, and an agreement was less robust in assessing UC patients' mild to moderate disease activity. However, the strength of the association varies by ethnic background. Hence, caution should be exercised when using the PUCAI score to assess UC disease activity in Hispanic pediatric patients.